Menyingkapi Penurunan Kepercayaan Masyarakat Terhadap Aparat Penegak Hukum Di Indonesia - Gilang Putra; Kayus Kayouwan Lewoleba (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
In Indonesia, the main challenge in achieving the principle of the rule of law is unfair legal practices, where some powerful and rich people can manipulate the legal system for their personal interests. This situation hinders efforts to ensure justice for all people. Therefore, high legal awareness among the public and law enforcers is very important to realize the principle of the rule of law. Bureaucratic reform and the implementation of a code of ethics for law enforcers are essential steps in creating an environment that is more transparent and responsible for the legal needs of society. By carrying out this reform, it is hoped that law enforcement can become more consistent, fair and clear. Through consistent, fair and clear law enforcement, it is hoped that Indonesian society can move from dependence on the law out of fear, towards obedience based on a deep understanding of the importance of the law in maintaining order and social justice. This is a crucial step in building a society that truly obeys the law, with belief in the principles of justice championed by the legal system.